Parenting Consensual Non-Monogamists’ Perceptions of the Conciliation of their Parenting and Sexual Lifestyle Roles - Avanthay Strus, Jacqueline; Polomeno, Viola (Aporia, 2026)
This article presents partial results of a mixed methods study about consensual non-monogamists’ perceptions of conciliating their parenting and sexual lifestyle roles. By using the Expanding the Movement for Empowerment and Reproductive Justice Lens that was enhanced by Cowan and Cowan’s Ecological Model of the Transition to Parenthood, six participants completed an online questionnaire and a semi-structured interview. The qualitative results reveal that parenting consensual non-monogamy contains three phases: contemplating consensual non-monogamy, acting on it, and incorporating it during parenthood. The conciliation of roles depends on family functioning, effective communication, and social support, yet participants found diverse ways to return to their sexual lifestyle. The quantitative results from the Parenting Role-Sexual Role Conciliation Scale support the qualitative ones. Perinatal nurses and allied health care professionals need to know about parenting consensual non-monogamists and how they conciliate their parenting and sexual lifestyle roles.